Any Role of High-Dose Vitamin C for Septic Shock in 2021? - Agarwal, Ankita; Hager, David N.; Sevransky, Jonathan E. (Seminars in Respiratory and Critical Care Medicine, 2021)
While the use of vitamin C as a therapeutic agent has been investigated since the 1950s, there has been substantial recent interest in the role of vitamin C supplementation in critical illness and particularly, sepsis and septic shock. Humans cannot synthesize vitamin C and rely on exogenous intake to maintain a plasma concentration of approximately 70 to 80 μmol/L. Vitamin C, in healthy humans, is involved with antioxidant function, wound healing, endothelial function, and catecholamine synthesis. Its function in the human body informs the theoretical basis for why vitamin C supplementation may be beneficial in sepsis/septic shock.Critically ill patients can be vitamin C deficient due to low dietary intake, increased metabolic demands, inefficient recycling of vitamin C metabolites, and loss due to renal replacement therapy. Intravenous supplementation is required to achieve supraphysiologic serum levels of vitamin C. While some clinical studies of intravenous vitamin C supplementation in sepsis have shown improvements in secondary outcome measures, none of the randomized clinical trials have shown differences between vitamin C supplementation and standard of care and/or placebo in the primary outcome measures of the trials. There are some ongoing studies of high-dose vitamin C administration in patients with sepsis and coronavirus disease 2019; the majority of evidence so far does not support the routine supplementation of vitamin C in patients with sepsis or septic shock.
Keywords: ascorbic acid; HAT Rx; resuscitation; sepsis; septic shock; vitamin C